Reliability of the 15-s Maximal Lactate Accumulation Rate (VLamax) Test for Cycling - Christopher R. Harnish; Thomas C. Swensen; Deborah King (Physiologia, 2023)
Background: The purpose of this study is to ascertain the reliability of two 15-s sprint cycling tests in men and women to estimate the maximum lactate accumulation rate (VLamax). Methods: Eighteen men and twelve women completed two sprint sessions over 1 week. A 10 min warm-up preceded the obtaining of a 3 µL blood lactate (BLC) sample, after which a 15 s sprint was completed; cyclists then rested passively while multiple lactate samples were taken until the levels peaked. Trial differences and reliability across trials were analyzed using a paired-sample t-test, Pearson’s correlation, Intraclass correlation (ICC), and Bland–Altman analysis with α = 0.05 for all tests; data are reported as mean ± sd. Results: Power (W) was similar across trials (773.0 ± 143.5 vs. 758.2 ± 127.4; p = 0.333) and the coefficient of variation (CV) of 4.7%. VLamax (mM·L−1·s−1) was similar (0.673 ± 0.024 vs. 0.635 ± 0.237; p = 0.280), but only moderately reliable across trials with CV, ICC, and R values of 18.6%, 0.661, and 0.67, respectively. Pre-BLC and peak BLC CV were 45.6 and 23.3%, respectively. Conclusions: A 15 s VLamax cycling sprint is moderately reliable, possibly affected both by the lactate measurement and other variables used in the calculation. More research may offer ways to improve reliability.